The Recent Environmental History, Attempted Restoration and Future Prospects of a Challenged Lobelia Pond in Northeastern Belgium - Luc Denys; Jo Packet; An Leyssen; Floris Vanderhaeghe (Diversity, 2024)
Softwater ponds with Lobelia dortmanna (EU habitat type 3110) represent the rarest aquatic habitat in Belgium. As in many other European countries, its unfavourable conservation status necessitates restoration according to the EU Habitats Directive, which is compromised by a range of pressures and faces increasing social–economic opposition. To explore appropriate goals and remaining obstacles for its ecological rehabilitation, we investigated the environmental history of a pond, formerly renowned for the occurrence of this habitat. We complemented monitoring data with information inferred from diatoms analysed from old samples, herbarium specimens and surface sediments, vegetation records, physical–chemical analyses and additional observations. This indicated almost circumneutral, slightly buffered and nutrient-poor conditions for the first decades of the 20th century. Deposition of atmospheric pollutants caused gradual acidification from the early 1940s, intensifying into mineral-acidic conditions by the 1970s. More recently, a period of alkalinisation and eutrophication followed despite some restoration efforts. We discuss these changes in the contexts of general setting, external pressures and internal processes. Reflecting upon the prospects for restoring the pond’s emblematic biodiversity, management implications for this and other softwater sites dealing with similar problems are discussed. A new combination in the diatom genus Iconella is proposed.